Autoimmune Pathology as Predisposing Factor of the Change in Cryosensitivity of Lymphohemopoietic Complex Cells - Goltsev, A. N.; Kozlova, Yu. A. (Problems of Cryobiology and Cryomedicine, 2003)
There are presented data on the changes in structural and functional parameters of cells of lymphohemopoietic complex (LHPC) under the development and maintaining in an organism of pathological process. The attention was paid to the fact of considerable modulation of initial state of LHPC cells at molecular, cellular levels during the development of autoimmune diseases (AIDs). These data should be taken into account when elaborating the cryopreservation regimens for the cells in an organism and with developing pathology of any form. Â 